Effect of glutaraldehyde as crosslinker on the properties of cellulose nanocrystal/chitosan films. Issue 1 (October 2020) - Gan, Pei Gie; Sam, Sung Ting; Omar, MohdFirdaus; Abdullah, Mohammad Faiq
Abstract: Cellulose nanocrystals (CNC) were isolated from the empty fruit bunch as the reinforcing filler to enhance the tensile and thermal properties of chitosan films. The addition of CNC has greatly increased the tensile strength of the chitosan films from 32.9 MPa for neat chitosan film to 50.9 MPa for 5 wt% CNC/chitosan films. The addition of glutaraldehyde as crosslinker has further improved the tensile property of chitosan films. However, the incorporation of CNC and glutaraldehyde has a negative effect on the elongation at break of the films due to restricted polymer chain mobility. Besides, the addition of CNC also enhanced the melting temperature of the chitosan films. The crosslinking process has further increased the melting temperature to 112.8°C with the addition of 5 wt% CNC. Therefore, the crosslinked CNC/chitosan films display greater property reinforcements than non-crosslinked films.